Examining the Performance Implications of Design Patterns in Front-end Web Development: A Preliminar Comparative Study with React and Vue.js - Gomes, Francisco; Soares, Pamella; Araújo, Allysson Allex (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2023: Proceedings of the 29th Brazilian Symposium on Multimedia and the Web, 2023)
With the increasing use of design patterns as well as front-end libraries and frameworks in web development, understanding the computational trade-offs associated with their adoption is essential. In this sense, this paper discusses the preliminary research results focusing on the performance implications of design patterns using React and Vue.js. Through a computational experiment, we analyzed a web application’s memory consumption, CPU usage, rendering time, and response time with five design patterns implemented. The findings contribute to a better understanding of the trade-offs associated with design pattern adoption and provide valuable insights for developers and organizations seeking to optimize the performance of their web applications.